The Approach to Diagnosis and Treatment of Chronic Constipation: Suggestions for a General Practitioner - Pierre Paré (Canadian Journal of Gastroenterology)
Chronic constipation is a frequent complaint. Symptoms of obstructive defecation (straining, hard and lumpy stools, or incomplete evacuation) are more frequent and bothersome than the frequency of bowel movements. Patient assessment is clinically based on the presence or absence of red flags. Commonly used therapies (eg, bulk-forming agents, stool softeners and stimulant laxatives) have only been evaluated in small studies of short duration. Polyethylene glycol was shown to be effective and safe in several rigorous trials with durations of more than one year. New drugs (prucalopride, lubiprostone and linaclotide) were shown to be effective and safe in well-designed and rigorous studies. Trials conducted in primary care patients are lacking for all therapies. Biofeedback and behavioural therapies are effective, but should be reserved for selected patients after proper diagnostic evaluation. A practical management algorithm is proposed using a multistep approach favouring early introduction of combined therapies and long-term step-down strategy to the lowest satisfactory regimen.